The Current Development Status of Marine Engine Fault Diagnosis Technology - Fu, Yongkang (International Journal of Mechanical and Electrical Engineering, 2025)
As the core equipment of the ship power system, the operational reliability of the Marine engine is directly related to the safety and energy efficiency of ship navigation. With the increase in the complexity of Marine engineering systems and the growing demand for intelligence, the traditional fault diagnosis methods that rely on manual experience can no longer meet the needs of modern ship engineering. In recent years, breakthroughs in signal processing technology, artificial intelligence algorithms and multi-source data fusion technology have driven the innovation of Marine engine fault diagnosis technology. This paper systematically reviews the research progress and challenges in the field of Marine engine fault diagnosis from aspects such as the technological development history, core methods, experimental verification and future trends.